Differences between Sanatan Hindu and Buddha’s Teaching (Research Nepal Journal of Development Studies, 2019)
The basic philosophy between Sanatan Hindu and Buddha’s teaching is the study of humanity for emancipation. Most of the hardliner Buddhists and some communal by birth Brahman are dividing the people in two sects. Sanatan Nepali Hinduism and Original Nepali Buddhism cannot be separated. Politically contaminated so called scholars are dividing and manipulating the fact. Honestly, Swyamhu is Shambhu and Pashupatinath is Buddha. Both the ideologies are simply a vehicle to emancipate human life. To find out the basic differences between two philosophies from selected two texts, the study is being conducted.